Effect of number of blades on aerodynamic forces on a straight-bladed Vertical Axis Wind Turbine. (October 2015) - Li, Qing'an; Maeda, Takao; Kamada, Yasunari; Murata, Junsuke; Furukawa, Kazuma; Yamamoto, Masayuki
Abstract: Small wind turbine performance and safety standard for straight-bladed Vertical Axis Wind Turbine (VAWT) have not been developed in the world because of the lack of fundament experimental data. This paper focuses on the evaluation of aerodynamic forces depending on several numbers of blades in wind tunnel experiment. In the present study, the test airfoil of blade is symmetry airfoil of NACA 0021 and the number of blades is from two to five. Pressure acting on the surface of rotor blade is measured during rotation by multiport pressure devices and transmitted to a stationary system through wireless LAN. And then, the aerodynamic forces (tangential force, normal force et al.) are discussed as a function of azimuth angle, achieving a quantitative analysis of the effect of numbers of blades. Finally, the loads are compared with the experimental data of six-component balance. As a result, it is clarified that the power coefficient decreases with the increase of numbers of blades. Furthermore, the power which is absorbed from wind by wind turbine mainly depends on upstream region of azimuth angle of θ  = 0°∼180°. In this way, these results are very important for developing the simple design equations and applications for straight-bladed VAWT. Highlights: Aerodynamic forces are measured by not only torque meter but also six-component balance. The pressure distribution on the surface of rotor blade is directly measured by multiport pressure devices. The power coefficient decreases with the increase of numbers of blades. The fluctuation amplitudes from six-component balance show larger value than the results of pressure distribution.